Finite element model focused on stress distribution in the levator ani muscle during vaginal delivery - Krofta, Ladislav; Havelková, Linda; Urbánková, Iva; Krčmář, Michal; Hynčík, Luděk; Feyereisl, Jaroslav (International urogynecology journal, 2017)
INTRODUCTION AND HYPOTHESIS: During vaginal delivery, the levator ani muscle (LAM) undergoes severe deformation. This stress can lead to stretch-related LAM injuries. The objective of this study was to develop a sophisticated MRI-based model to simulate changes in the LAM during vaginal delivery. METHODS: A 3D finite element model of the female pelvic floor and fetal head was developed. The model geometry was based on MRI data from a nulliparous woman and 1-day-old neonate. Material parameters were estimated using uniaxial test data from the literature and by least-square minimization method. The boundary conditions reflected all anatomical constraints and supports. A simulation of vaginal delivery with regard to the cardinal movements of labor was then performed. RESULTS: The mean stress values in the iliococcygeus portion of the LAM during fetal head extension were 4.91-7.93 MPa. The highest stress values were induced in the pubovisceral and puborectal LAM portions (mean 27.46 MPa) at the outset of fetal head extension. The last LAM subdivision engaged in the changes in stress was the posteromedial section of the puborectal muscle. The mean stress values were 16.89 MPa at the end of fetal head extension. The LAM was elongated by nearly 2.5 times from its initial resting position. CONCLUSIONS: The cardinal movements of labor significantly affect the subsequent heterogeneous stress distribution in the LAM. The absolute stress values were highest in portions of the muscle that arise from the pubic bone. These areas are at the highest risk for muscle injuries with long-term complications.
Keywords: Imaging, Three-Dimensional; Finite Element Analysis; Magnetic Resonance Imaging; novorozenec; Infant, Newborn; distorze a distenze; magnetická rezonanční tomografie; Pregnancy; Humans; Models, Anatomic; Head; Sprains and Strains; Female; pánevní dno; dospělí; lidé; hlava; Fetus; Adult; plod; kosterní svaly; pružnost; Pelvic Floor; ženské pohlaví; vedení porodu; Delivery, Obstetric; Muscle, Skeletal; těhotenství; Elasticity; zobrazování trojrozměrné; biomechanika; Biomechanical Phenomena; anatomické modely; analýza metodou konečných prvků